(untitled) (Journal of Applied Oral Science, 2006)
OBJECTIVE: To assess fluoride (F-) intake from water and toothpaste by children aged 18 to 36 months and to monitor the F- concentrations in the drinking water system in a tropical city of Brazil. METHODS: Children (n=58) aged 18-36 months, all lifetime residents of Penedo, state of Alagoas, Brazil, participated in this study. Water F- analyses were carried out in 7 different occasions at least a week apart. For 2 days all the water drunk by each child was accounted for. Fluoride intake from water for each child was estimated using the mean F- concentration of water in 7 different occasions. Fluoride intake from toothpaste was estimated by subtracting the recovered post-brushing F- from the original amount placed in the toothbrush. The F- intake from water and toothpaste was estimated by dividing the total amount of F- ingested by the weight of each child. RESULTS: The mean F- concentration in the drinking water was 0.94 ppm (mean range 0.78-1.1 ppm), which is above the 0.7 ppm recommended for this area of Brazil. Mean total F- intake from water and toothpaste was 0.128 mg F-/Kg Body Weight/day. The daily means of F- intake from water and toothpaste were 0.021 and 0.107 mg F-/Kg Body Weight, respectively. Ninety six percent of children showed F- intake above 0.07 mg F-/Kg Body Weight/day. CONCLUSIONS: Children in Penedo are at risk for developing dental fluorosis due to high F- intake from fluoridated toothpastes. Water fluoridation showed low contribution to the total F- intake. However, high water F- concentrations in the water indicate the need of surveillance of the artificial water fluoridation system.